2017
DOI: 10.1597/14-128
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Identification of Fetal Tooth Germs

Abstract: We recommend using this method as the first exam to evaluate fetal morphology and also to help establish accurate diagnosis of abnormalities in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…In accordance with the literature available at the beginning of our study, the number of tooth germs was considered to be reduced if it was below six in at least one alveolar bone . A recent study by Seabra et al showed that in many fetuses, 10 tooth germs per alveolar bone can be visualized sonographically; this threshold should, however, not be applied to the prenatal screening for XLHED in a cohort of pregnant women with known EDA mutation: the risk of a false positive result would increase and concomitantly the risk of treating an unaffected fetus.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…In accordance with the literature available at the beginning of our study, the number of tooth germs was considered to be reduced if it was below six in at least one alveolar bone . A recent study by Seabra et al showed that in many fetuses, 10 tooth germs per alveolar bone can be visualized sonographically; this threshold should, however, not be applied to the prenatal screening for XLHED in a cohort of pregnant women with known EDA mutation: the risk of a false positive result would increase and concomitantly the risk of treating an unaffected fetus.…”
Section: Discussionmentioning
confidence: 60%
“…In accordance with the literature available at the beginning of our study, the number of tooth germs was considered to be reduced if it was below six in at least one alveolar bone 22,23. A recent study by Seabra et al20 showed that in many fetuses, 10 tooth germs per alveolar bone can be visualized sonographically; this threshold should, however, not be applied to the prenatal screening for XLHED in a cohort of pregnant women with known EDA mutation: the risk of a false positive result would increase and concomitantly the risk of treating an unaffected fetus.Considering the specificity of 100%, tooth germ sonography would be well suitable for identifying patients to be treated in utero by intraamniotic administration of an EDA1 replacement molecule, particularly because it does not expose the fetus or the mother to any procedure-related risk. The approach was applicable in different countries at various sites representing different levels of care, in university hospitals as well as in private medical centers.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Tooth germ sonography may, however, be applicable more broadly. Prenatal assessment of facial features via two-dimensional ultrasound has become an important part of screening for fetal abnormalities; because oligodontia is associated with fetal pathology in a substantial number of cases, visualization of alveolar structures has been assigned a larger role in prenatal diagnostics 28 . Of course we recognise that in these circumstances -without a prior indication of EDA gene involvement -the measures of test performance reported here will not apply, because the prior probability that the cause is a pathogenic variant in EDA will be so much smaller.…”
Section: Discussionmentioning
confidence: 99%